Family Firm Heterogeneity and Tax Avoidance: The Role of the Founder. (September 2019) - Brune, Alexander; Thomsen, Martin; Watrin, Christoph
Family business research suggests that the population of family firms cannot be regarded as a homogenous group. Therefore, with respect to tax avoidance, we analyze the role of the founder as one dimension of family firm heterogeneity. Specifically, we consider socioemotional wealth loss aversion and find that founders may affect the level of tax avoidance not only when they have direct influence (i.e., serving as CEO) but also when they possess solely indirect influence (i.e., having substantial ownership or a seat on the board). Overall, our results suggest that founders remain attached to their firms despite giving up executive positions.